Dancing the Other in South Africa - Samuel, Gerard M (School of Dance, 2017)
At the centre of discourse of Dance in South Africa is the notion of Other. The form and approach in Contemporary Dance in South Africa in the 21st century has been shaped by cultural forces such as apartheid and colonialism. This thesis sets out a phenomenological study of Othering in Dance in South Africa through a hermeneutical unpacking of 'Older dancing'. Its critical question grapples with the notion of age as a new marker of alterity in Dance and asks: How does dancing the Other bring new ways of seeing bodies? The lived experiences of four categories in Older dancing: dancers, choreographers, directors and dance critics, in and outside of South Africa since the 2000s, will be analysed. My own position in each of the categories above has allowed me to participate in Contemporary Dance and the performing arts field in South Africa for over 45 years. A partial history of Contemporary Dance in South Africa is explicated in order to provide paradigmatic frames for this study. The philosophical enquiry of this thesis has foregrounded Dance Studies as a discrete research field in order to highlight dance and the body itself, and to reassert an enviable position of dancing bodies as research instruments and knowledge producers. A hermeneutical narrative analysis was deployed following twelve interviews that were conducted over 4 years (2012-2014). Seven South African and five non-South African 'voices' were analysed and coded against four primary lines of enquiry in Experience: notions of cultural inscription and dancing bodies as blank slates; questions of (in)visibility and frailty of older persons, wisdom and (in)dependent older dancers and the ontologies of marginalisation for Older dancing within concert theatre Dance. This suggested a thesis of wider Body-space reading and continuum for Dance that could be useful in understanding epistemology of prejudice. Recommendations that flow from this study will relate to Dance Studies in South Africa that is already moving away from its anthropological roots in tribal dances, experimentations with multicultural dance, towards unpacking intersectionality, public art and the contested label African dance. It provides Body-space as a further theoretical tool with which to observe dancing and bodies as states of becoming that will be of interest to Dance Studies, Performance Theory and Cultural Studies.